Clinical outcomes of phenotype-guided treatment in group D carbapenemase-producing Enterobacterales bacteremia - Jinghao Nicholas Ngiam; Matthew Chung Yi Koh; Nicholas Jian Hao Chan; Jeanette Teo; Ka Lip Chew (Microbiology Spectrum)
ABSTRACT International guidance recommends ceftazidime-avibactam for OXA-48-type carbapenemase-producing Enterobacterales (OXA-48-CPE) infections. However, OXA-48-CPE lacking extended spectrum and AmpC β-lactamases may remain susceptible to third-generation cephalosporins (3GC), potentially allowing treatment without avibactam. OXA-23 also has variable hydrolytic activity against 3GC. This study reviewed the outcomes of OXA-CPE bloodstream infections treated based on phenotypic susceptibility testing. A retrospective review of OXA-48-CPE and OXA-23-CPE bloodstream infections was conducted from February 2022 to July 2024. Data on antimicrobial susceptibility, patient background, infection source, treatments, and outcomes were analyzed. Whole-genome sequencing (WGS) determined the presence of β-lactamase genes in available isolates. Ten bloodstream infection episodes occurred in nine patients (eight OXA-48-like Escherichia coli [n = 4], Klebsiella pneumoniae [n = 4], and one OXA-23-CPE Proteus mirabilis), with a urinary source in 44.4% (n = 4). Of the isolates, 5/9 (55.5%) were 3GC-susceptible. WGS did not identify any extended-spectrum β-lactamases in these isolates. Three 3GC-susceptible cases (two OXA-48 and one OXA-23) were successfully treated with ceftriaxone. Among the 3GC-resistant cases, two were treated with ceftazidime-avibactam, and two with high-dose meropenem alone or in combination with aztreonam. One recurrence was observed in a case treated with ceftazidime-avibactam. Mortality was low, with one death reported in a patient treated with ceftazidime-avibactam. In this small study, 55.5% of OXA-48-CPE and OXA-23-CPE isolates retained 3GC susceptibility. When used for therapy, 3GC and non-β-lactam antibiotics demonstrated clinical efficacy where antibiotic susceptibility was demonstrated.IMPORTANCEThe Infectious Diseases Society of America guidance document recommends the use of ceftazidime-avibactam for the treatment of OXA-48-type carbapenemase-producing Enterobacterales (OXA-48-CPE). However, this antibiotic is expensive and not always available in some settings. The clinical outcomes of OXA-48-CPE and OXA-23-CPE bloodstream infections when treated with third-generation cephalosporin (3GC) remain unclear. Among 10 episodes in nine patients, we found that five isolates (55.5%) were 3GC-susceptible, with three cases successfully treated with ceftriaxone. Whole-genome sequencing demonstrated the absence of extended-spectrum β-lactamases in the 3GC-susceptible isolates, which aligns with phenotypic 3GC susceptibility. Mortality was low (1/9). Many OXA-48-CPE and OXA-23-CPE infections retain 3GC susceptibility, raising the possibility that these agents may be viable alternatives to ceftazidime-avibactam in select cases.